Production of nanoparticles by polyelectrolyte complexation from novel locust bean gum cationic derivatives - Rodrigues, Miguel Viegas (2021)
Nanoparticles have a wide array of uses, one of which is drug delivery. Nanoparticle drug delivery systems have advantages over conventional drug delivery systems, as they are able to increase bioavailability, solubility and permeability of drugs, while also offering the possibility of targeted delivery and controlled release. The preparation of nanoparticles can follow different procedures, including polyelectrolyte complexation, based on electrostatic interaction of oppositely charged polymers, which was used in this work. There are currently a wide number of anionic polysaccharides to choose from, either from seaweed, animals or microorganisms. Still, when it comes to cationic polysaccharides, the most common choice is chitosan. For this reason, the chemical modification of polysaccharides for obtaining positively-charged derivatives is worth exploring. The main objective of this work was to explore different strategies to chemically modify locust bean gum in order to obtain a cationic polyelectrolyte that, by complexation with carrageenan, affords nanoparticles with the potential for application in the development of drug delivery systems. To achieve this, it was attempted to oxidize locust bean gum to the corresponding aldehyde using different oxidizing reagents and then, by reductive amination, insert amino groups in the polysaccharide structural units. The different oxidation reagents were sodium periodate, TEMPO, Oxone® and ammonium persulfate. All obtained derivatives were analyzed through FTIR spectroscopy to access the success of each reaction. NMR analysis was also performed on amino locust bean gum obtained from periodate oxidized gum, which seemed to indicate a high degree of depolymerization during the reductive step. Nanoparticle production was possible using amino locust bean gum obtained from periodate oxidized gum and carrageenan at mass ratios of 4/1, 1/3 and 1/4. These particles showed similar size, zeta potential and PdI as other locust bean gum based nanoparticles, albeit with a larger deviation.